ANALISIS PENDAPATAN DAN ALTERNATIF PENDAPATAN BRITISH SCHOOL JAKARTA - Istiqomah, Nur Nasichah; Rifa’i, Rifa’i; Munadi, Muhammad (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
This study analyzes the revenue sources and alternative income generation at British School Jakarta (BSJ) for the fiscal years 2023 and 2024. The background of this research is the growing need for financial sustainability in educational institutions, which often rely heavily on tuition fees. The focus of the study is on revenue diversification and alternative income streams to support the school’s operational and developmental activities. The research employed a library research method, with data collected from BSJ’s annual financial reports for 2023 and 2024. Data were analyzed through data reduction, data presentation, and drawing conclusions to identify the main and alternative sources of revenue. The research results show that BSJ's revenue sources come from education fees, capital contribution fees, interest income, and other income. Based on the school's annual financial report, BSJ experienced a financial surplus of 43.7 billion in 2023 and a financial surplus of 48.1 billion in 2024. This figure was influenced by the increase in the number of students to 1,412, or 2% more than the previous year. BSJ's alternative income consists of interest income and other income. BSJ's alternative income also contributed to BSJ's financial surplus because investment income increased 50% more than the previous year. This study provides insight into the importance of income diversification as an effort to maintain school sustainability. Revenue diversification has been implemented by the British School Jakarta through deposits and bonds. This opens new insight that investing school capital is permissible as long as it does not disrupt the school's operational funds. ABSTRAK Penelitian ini menganalisis tentang sumber pendapatan dan alternatif pendapatan di British School Jakarta (BSJ) pada tahun 2023 dan 2024. Fokus kajian meliputi diversifikasi pendapatan dan alternatif pendapatan pada BSJ. Metode penelitian ini menggunakan pendekatan penelitian kepustakaan, teknik analisis data dilakukan dengan reduksi data, penyajian data dan penarikan kesimpulan. Data diolah dari laporan keuangan tahunan sekolah. Hasil penelitian menunjukkan bahwa sumber pendapatan BSJ berasal dari biaya pendidikan, kontribusi iuran modal, pendapatan bunga, dan pendapatan lain-lain. Berdasarkan laporan keuangan tahunan sekolah, BSJ mengalami surplus keuangan sebesar 43,7 miliar pada 2023 dan surplus keuangan sebesar 48,1 miliar pada 2024. Nominal tersebut dipengaruhi oleh kenaikan jumlah siswa menjadi 1.412 atau 2% lebih banyak dari tahun sebelumnya. Alternatif pendapatan BSJ terdiri dari pendapatan bunga dan pendapatan lain-lain. Alternatif pendapatan BSJ juga turut berkontribusi pada surplus keuangan BSJ pasalnya pendapatan investasi meningkat 50% lebih banyak dari tahun sebelumnya. Studi ini membuka wawasan bahwa diversifikasi pendapatan sebagai upaya menjaga keberlanjutan sekolah penting dilakukan. Diversifikasi pendapatan sudah diterapkan oleh British School Jakarta melalui deposito dan obligasi. Hal ini membuka wawasan baru bahwa menginvestasikan modal sekolah diperbolehkan asalkan tidak mengganggu dana operasional sekolah.